O som das telas: censura às trilhas sonoras musicais dos filmes produzidos durante a ditadura civil-militar (1964-1985) - Ribeiro, Eloah Varga (2022)
The period of the civil-military dictatorship (1964-1985) was marked by harsh censorship of films and music, because they were seen as subversive or for attacking the “moral” imposed by the regime. Both categories have large studies that investigate these censors, however, the soundtracks of censored films are rarely mentioned in these studies. Therefore, the objective of this work was to map the films whose soundtracks suffered some kind of censorship during the aforementioned period, and in this mapping to search for reasons for censorship, and the censored music. The research process was carried out in documentary sources of the period, in order to locate documents whose censors' opinion indicated musical soundtracks and select from the bibliography on cinema and music notes on the censorship of films related to music. The first results showed that there is a gap when the subject is film soundtracks, and that the censorship carried out on films during the dictatorial period did not refer to music. Therefore, it was necessary to search for another source, the digital collection of the National Library. What is evident is that this area of approach to the dictatorial period is still very little researched, and there is a clear need for more incisive analyzes to try to answer the questions raised during the research. With the work carried out, it was possible to perceive the lack of bibliography and the permanence of questions that this theme addresses.